Developing an understanding of networks with a focus on LMIC health systems: how and why clinical and programmatic networks form and function to be able to change practices: a realist review - Kalaris, K; English, M; Wong, G (Elsevier, 2023)
Networks are an increasingly employed approach to improve quality of care, service delivery, and health systems performance, particularly in low-and-middle income country (LMIC) health systems. The literature shows that networks can improve the provision and quality of services and health system functioning but there is limited evidence explaining how and why networks are established and work to achieve their reported results. We undertook a realist review to explore this. The objective of this realist review was to develop a programme theory outlining the underlying mechanisms and interactions of contexts that explain how and why a network’s set-up and function enable high-quality care and services and improved clinical outcomes in LMIC health systems. We followed Pawson’s five steps for realist reviews. The search strategy was based on a previously published scoping review with additional searches. Literature was selected based on its relevance to the programme theory and rigour. Context-mechanism-outcome configurations were developed from the extracted data to refine the initial programme theory with causal explanations. Theories on social movements and organisations supported the identification of mechanism and brought additional explanatory power to the programme theory. The programme theory explains how networks are initiated, formed, and function in a way that sets them up for network leadership and committed, engaged, and motivated network members to emerge and to change practices, which may lead to improved quality of care, service delivery, and clinical outcomes through the following phases: identify a problem, developing a collective vision, taking action to solve the problem, forming purposeful relationships, linkages, and partnerships, building a network identity and culture, and the creation of a psychological safe space. This deeper understanding of networks formation and functioning can lead to a more considered planning and implementation of networks, thereby improving health system functioning and performance.